Aspek Finansial Pengembangan KomoditasPisang Hias (Heliconiasp.) Di Sekar Bumi Tropical Farm & Florist Desa Kerta, Kecamatan Payangan, Kabupaten Gianyar - TRIYULIANTI, KOMANG; SUDARMA, MADE; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Financial AspectOrnamental Banana( Heliconia sp.) InSekarBumi Tropical Farm& Florist at KertaVillage , Payangan District ,Gianyar Regency Heliconia flowernewlydevelopedcommodity , in 2011it’sproductionamounted to936 426stalksor25 % of allcommodities of cut flowersinBali province . The purposeof this researchincludesthe prospectsof Heliconia flowerin termsoffinancial aspect , marketingaspectandconstraintsencountered in the developmentof commodityinSekarBumi atKertaVillage , Payangan District ,Gianyar Regency . The results showedHeliconiaflower businessinSekarBumiFarm is feasiblebased on the financialaspect.Thisagribusinessinvestmenthasto fill several criteria , among others, the NetB/C > 1is Rp 1.48 , NPV > 0is RP 153.332.226,73 ,IRR > discount factorof 18% , which is22.38 % andpaybackperiodless than productive of this plant( 10 years ) is5,32years . Sensitivity analysisshowedthat development of Heliconia is no longer feasible to conduct if the increase cost of labor is more than 3% or the revenue falls below 14% . The problemsfaced in this business , consist oftwofactors:internal and external factors . Internal factorsincludelack of capitalinvestmentandlimited number of varietiesof the plants . While, the external factor is competitionwithimported productsand from outside region .It is suggested that SekarBumiFarmmanagerstoincreaseHeliconiaflowertypesand to expand the marketingnetwork . Keywords : Heliconia , InvestmentCriteriaAnalysis , Prospects , FinancialAspect , AspectMarketing .